Influence of source of calories on composition and production of milk - Gallegos, A.J.; Shirley, John E. (Kansas Agricultural Experiment Station, 2011)
Wheat and tallow increased milk production in a complementary fashion when added to a milo-based grain mix.
Keywords: Concentrate mixes; Tallow; Wheat; Milo; Milk yield